The Theology Of Knowledge: A Study On The Definition Of Knowledge Among The Early Mutakallimun - Mohd Radhi Ibrahim (Jabatan Akidah & Pemikiran Islam Akademi Pengajian Islam Universiti Malaya, 2024)
Indexed by WOS